2014
DOI: 10.1371/journal.pone.0103525
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of RNA Transcripts during Neuronal Maturation and Ischemic Injury

Abstract: Neuronal development is a pro-survival process that involves neurite growth, synaptogenesis, synaptic and neuronal pruning. During development, these processes can be controlled by temporal gene expression that is orchestrated by both long non-coding RNAs and microRNAs. To examine the interplay between these different components of the transcriptome during neuronal differentiation, we carried out mRNA, long non-coding RNA and microRNA expression profiling on maturing primary neurons. Subsequent gene ontology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…We found that the expression of miR-140-5p to be increased in IFG as well as in T2DM, in both the human and rat miRNA microarray analyses, as well as in our in vitro study, where miR-140-5p level increased with increasing glucose concentrations ( Table 1 and Table S2 [ 72 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ]). This increase was also found to correlate with the increase in apoptosis ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the expression of miR-140-5p to be increased in IFG as well as in T2DM, in both the human and rat miRNA microarray analyses, as well as in our in vitro study, where miR-140-5p level increased with increasing glucose concentrations ( Table 1 and Table S2 [ 72 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ]). This increase was also found to correlate with the increase in apoptosis ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Primary antibodies used were mouse anti-parvalbumin 25 (1:1000 dilution, p3088, Sigma-Aldrich, St. Louis, MO), rabbit anti-VGAT 21 (1:2000 dilution, 131003, Synaptic Systems, Germany), rabbit anti-somatostatin 26 (1:300 dilution, sc-13099, Santa Cruz Biotechnology, Santa Cruz, CA), mouse anti-NeuN 27 (1:1000 dilution, ab104224, Abcam, Cambridge, MA) and mouse anti-ubiquitin 28 (1:500 dilution, 3936, Cell Signaling Technology, Beverly, MA). Secondary antibodies used were Alexa Fluor 647 donkey anti-mouse IgG 29 (1:300 dilution, 715-605-150, Jackson ImmunoResearch Laboratories, West Grove, PA) and Alexa Fluor 647 donkey anti-rabbit IgG 30 (1:300 dilution, 711-605-152, Jackson ImmunoResearch Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…Primary cultures of cortical neurons were established from E15 Swiss albino mouse brains according to Hirai et al [ 28 ] with slight modifications performed by Kaur et al [ 29 ]. The cortices were dissected from E15 mouse embryos and washed with Hanks’ balanced salt solution (HBSS; Gibco, Invitrogen, USA).…”
Section: Methodsmentioning
confidence: 99%